Solid phase microextraction-comprehensive two-dimensional gas chromatography-time-of-flight mass spectrometry for the analysis of honey volatiles - Čajka, Tomáš; Hajšlová, Jana; Cochran, Jack; Riddellová, Kateřina; Klimánková, Eva (Journal of separation science, 2007)
Head-space solid phase microextration (SPME), followed by comprehensive two-dimensional gas chromatography-time-of-flight mass spectrometry (GCxGC-TOFMS), has been implemented for the analysis of honey volatiles, with emphasis on the optimal selection of SPME fibre and the first- and second-dimension GC capillaries. From seven SPME fibres investigated, a divinylbenzene/Carboxen/polydimethylsiloxane (DVB/CAR/PDMS) 50/30 microm fibre provided the best sorption capacity and the broadest range of volatiles extracted from the headspace of a mixed honey sample. A combination of DB-5ms x SUPELCOWAX 10 columns enabled the best resolution of sample components compared to the other two tested column configurations. Employing this powerful analytical strategy led to the identification of 164 volatile compounds present in a honey mixture during a 19-min GC run. Combination of this simple and inexpensive SPME-based sampling/concentration technique with the advanced separation/identification approach represented by GCxGC-TOFMS allows a rapid and comprehensive examination of the honey volatiles profile. In this way, the laboratory sample throughput can be increased significantly and, at the same time, the risk of erroneous identification, which cannot be avoided in one-dimensional GC separation, is minimised.
Keywords: Gas Chromatography-Mass Spectrometry; Time Factors; časové faktory; Temperature; Volatilization; volatilizace; med; mikroextrakce na pevné fázi; plynová chromatografie s hmotnostně spektrometrickou detekcí; teplota; Honey; Solid Phase Microextraction